Association between passive smoking and dental caries status in children: a cross-sectional analytical study - Dantham, Priyanka; Nuvvula, Sivakumar; Ismail, Ahmad Faisal; Akkilagunta, Sujiv; Mallineni, Sreekanth Kumar (Wroclaw Medical University, 2024)
Background. Several risk factors contribute to the development of dental caries in children, including sociodemographic, dietary, oral hygiene-related and other miscellaneous factors. Maternal smoking was highly associated with dental caries when compared to smoking by fathers or other household members.